Toddler Growth and Development of Pregnant Women Covid-19 - Jumadil, Juhriah; Budu, Budu; Ahmad, Mardiana; Alasiry, Ema; Sudirman, Jumrah; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Background: SARS-CoV-2 or also known as Coronavirus Disease 2019 (COVID-19) is a disease caused by a virus. This virus can affect the elderly, adults, children, infants and pregnant women, including breastfeeding mothers. Pregnant women as one of the vulnerable groups are at risk of viral infection because during pregnancy, the body physiologically and has the potential to affect organogenesis and fetal development. Direct exposure from the fetus to the mother's immune response from the mother due to infection during pregnancy may have the potential to impaired the growth and development of toddlers. Objective: This study aims to analyze the differences in the growth and development of toddlers from pregnant women infected with COVID-19 and those who are not infected with COVID-19. Methods: This study used a case control design , which was by comparing the case group and the control group with a sample of 148 consisting of 74 toddlers from pregnant women infected with COVID-19 and 74 toddlers from pregnant women who were not infected with COVID-19. The growth of toddlers was obtained by measuring weight and height in the growth and development graph using a developmental pre-screening questionnaire instrument (KPSP). Data analysis uses the Chi-Square and Mann Whitney tests. Results: In the growth of toddlers from the results analyzed from the two groups based on the weight of toddlers using the minimum weight gain value (KBM) with a p-value of 0.010 (p<0.05) means that there is a significant difference between the two groups, while the growth of toddlers based on height with a p-value of 0.337 (p>0.05) means that there is no significant difference between the two groups. In the development of toddlers from the results of statistical tests, the p-value of 0.282 (p>0.05) means that there is no significant difference between the two groups Conclusion: Toddlers born to pregnant women infected with COVID-19 can affect the weight of toddlers but have no effect on the height and development of toddlers